Progesterone Decreases Tyrosine Hydroxylase Phosphorylation State and Increases Protein Phosphatase 2A Activity in the Stalk-Median Eminence on Proestrous Afternoon - Liu, Bin (2009)
The progesterone (P(4)) rise on proestrous afternoon is associated with dephosphorylation of tyrosine hydroxylase (TH) and reduced TH activity in the stalk-median eminence (SME), which contributes to the proestrous prolactin surge in rats. In the present study, we investigated the time course for P(4) effect on TH activity and phosphorylation state, as well as cAMP levels and protein phosphatase 2A (PP2A) activity and quantity, in the SME on proestrous morning and afternoon. P(4) (7.5 mg/kg, sc) treatment on proestrous afternoon decreased TH activity and TH phosphorylation state at Ser-31 and Ser-40 within 1h, whereas morning administration of P(4) had no 1h effect on TH. PP2A activity in the SME was enhanced after P(4) treatment for 1h on proestrous afternoon without a change in PP2A catalytic subunit quantity, whereas P(4) treatment had no effect on PP2A activity or quantity on proestrous morning. Cyclic AMP levels in the SME were unchanged with 1h P(4) treatment. At 5h after P(4) treatment, TH activity and phosphorylation state declined coincident with an increase in plasma prolactin in both P(4)-treated morning and afternoon groups. PP2A activity in the SME was unchanged in 5h P(4)-treated rat. Our data suggest that P(4) action on tuberoinfundibular dopaminergic neurons involves at least two components. A more rapid (1h) P(4) effect engaged only on proestrous afternoon likely involves activation of PP2A. The longer P(4) action on tuberoinfundibular dopaminergic neurons is evident on both the morning and afternoon of proestrus and may involve a common, as yet unidentified, mechanism.